IDENTIFICATION OF TRAJECTORY INFORMATION BY APPLYING FUZZY AUTOMATIC CLASSIFICATION IN THE INFORMATION ASSOCIATION PROBLEM - A. V. Khizhniak; A. A. Belous; A. S. Bely (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Modern automated control systems of the air space are characterized by a large number of sources of radar data. Collection and compilation of data from them is a difficult task, aimed at creating a unified view of the air situation picture. One of the most difficult tasks in trajectory data unification is the identification of the trajectories of aerial objects based on data from multiple sources of orbital information. It is described an approach to solving the problem of trajectory data identification in algorithms for tracking aerial objects based on the application of the theory of fuzzy sets.